Purpura Fulminans in a 20-Year-Old Female - Alves,Francisca (2021)
ABSTRACT A previously healthy 20-year-old female presented with extensive retiform purpura located at the face, upper and lower limbs, one week after an episode of acute tonsillitis. Despite the exuberance of the cutaneous findings and progression to skin necrosis she had no accompanying symptoms. Laboratory investigation revealed a heterozygous protein C mutation (exon 9, c.1332G> C, p.Trp444Cys), accounting for a partial deficiency of this anticoagulant protein. The patient was started on broad spectrum antibiotics, anticoagulation and systemic corticosteroids, with no lesional progression and complete resolution of cutaneous ulceration within 6 months. This is a singular case of purpura fulminans, since two different causative factors precipitated the events. The previous tonsillitis reported by the patient is significant, because the serum concentration of protein S may also decrease after an infectious event - post-infectious purpura fulminans. This case illustrates that purpura fulminans due to autoantibodies against protein S, although rare, should be considered, especially in the absence of a severe acute infection. It also illustrates how in a given patient different independent factors can act simultaneously, triggering potentially devastating clinical scenarios.